Cross-modal correspondence : effect of vowel sounds on multiple shape properties - Ng, Kend Tuck (2015)
This study examined the cross-modal correspondences between speech sounds and visual stimuli, where past studies have reported associations between phonetic features and shape properties such as size and roundedness. However, some phonetic features of speech sounds in the English language are confounded with each other, as such, it is unclear which specific phonetic feature is responsible for the effect. This study thus introduces the non-English /y/ vowel to examine the relationship between the phonetic features of tongue height, tongue frontness/backness and lip rounding with three different shape properties (curvature, massiness and number of arms). Forty-eight undergraduates matched vowels to shapes in four different tasks. Results indicated that lip rounding was associated to curvy shapes while the absence of lip rounding was associated to spiky shapes. High resonating frequencies that corresponded with no lip rounding and tongue frontness were associated to smallness while low frequencies that corresponded with lip rounding and tongue backness were associated to largeness. Low tongue height was found to be associated with largeness in one of the tasks. In addition, the number of arms in a shape enhanced the effect of the curvature dimension only in rounded vowels. More research on other phonetic features and shape properties is needed to better understand the mechanisms behind cross-modal correspondences.